Favoritism and firms: Micro evidence and macro implications - Zareh Asatryan; Thushyanthan Baskaran; Carlo Birkholz; David Gomtsyan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We study the economic implications of regional favoritism, a form of distributive politics that redistributes resources spatially within countries. We use a large sample of enterprise surveys spanning across many low and middle income countries, and utilize transitions of national political leaders for identification. We document strong evidence of regional favoritism among firms located in close vicinity to leader's birthplaces but not in other regions, nor in home regions before leader's rise to power. Firms in favored regions become substantially larger in sales and employment, and also produce more output per worker, pay higher wages and, more generally, have higher total factor productivity. Furthermore, evidence from several mechanisms suggests that leaders divert public resources into their home regions by generating higher demand for firms operating in non-tradable sectors. A simple structural model of resource misallocation that is calibrated to match our empirical estimates implies that favoritism generates aggregat eoutput loss of 0.5% annually.
Keywords: D22; D72; O43; R11; 330; Regional favoritism; firm performance; enterprise surveys; resource misallocation